Aproveitamento de resíduos agroindustriais para indução dexilanases: clonagem e expressão do gene xyna1 de caulobacter crescentus e produção enzimática por delineamento experimental em aspergillus fumigatus fresen - Graciano, Luciana (2015)
The optimization of xylanase production of a new Aspergillus fumigatus Fresen strain (OI-1RT) was obtained by statistical approaches. The Plackett-Burman Design evaluation showed that the following components of Czapeck medium were biologically significant: sodium nitrate, potassium phosphate, magnesium sulfate and corn straw. These factors were selected to implement the 24 Central Composite Rotational Delineation with the proposed model validation. The response surface plots have indicated a trend for increased xylanase activity with increasing concentrations of maize straw. An additional test was carried out with different concentrations of maize straw and the optimized xylanase activity was 530 U ml-1 in the presence of 6.5% (w / v) of residual biomass, which was 11 times higher than the one obtained only with the Plackett-Burman Planning (45.8 U mL-1). The thermostability of the enzyme was kept at 90% at 50 °C for 6 hours. Enzyma tic hydrolyses tests were performed to obtain reducing sugars from maize straw, hydrolyzed maize straw and beechwood xylan. This procedure has been performed for 96 hours with 2 U ml-1 for xylanase (crude extract) and resulted in net production of 3.89, 20.96 and 21.64 μmol mL-1 for reducing sugars, respectively. This indicated possible biotechnological applications to the crude extract with xylan-degrading enzymes (xylanase).